2018
DOI: 10.15282/ijame.15.1.2018.8.0387
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrathin Film Between Two Molecularly Smooth Surfaces

Abstract: The forces between surfaces determine the properties of many biological systems. This makes them an important field of study. Measurements and numerical work of many researchers showed that in ultrathin lubricating films the net interaction between two surfaces separated by a polar lubricant involves both the electrostatic double layer force and the Van der Waals' force and at small separation solvation pressure is aided. In this work a numerical solution of the Reynolds' equation was developed using Newton-Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…According to the results, the load distribution on the engine main bearings and bearing shell deformation were affected by crankcase and crankshaft elasticities. Al-Samieh [13] developed a numerical solution of the Reynolds' equation using Newton-Raphson technique to obtain the film shape and pressure distribution caused by the hydrodynamic viscous action in addition to solvation pressure due to inter-surface forces. The numerical results showed that the effect of changing rolling speed and surface potential on the formation of ultrathin lubricating film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the load distribution on the engine main bearings and bearing shell deformation were affected by crankcase and crankshaft elasticities. Al-Samieh [13] developed a numerical solution of the Reynolds' equation using Newton-Raphson technique to obtain the film shape and pressure distribution caused by the hydrodynamic viscous action in addition to solvation pressure due to inter-surface forces. The numerical results showed that the effect of changing rolling speed and surface potential on the formation of ultrathin lubricating film thickness.…”
Section: Introductionmentioning
confidence: 99%